KANT’S CONCEPT OF THE HOLY WILL: A MORAL ARCHETYPE FOR RECONCILING HUMAN NATURE - Keberson Bresolin (Kriterion)
ABSTRACT This essay is devoted to a thorough analysis of the role and significance of the holy will in Kantian moral philosophy, highlighting its status as a crucial moral archetype and a pathway for reconciliation with human rational nature. By concentrating on the holy will, this paper illuminates its role as a normative model that not only sheds light on human capabilities and limitations within moral contexts but also advances a renewed understanding of freedom and duty. It is argued that the holy will, inherently aligned with moral laws and free from coercion, contrasts with the human will, which is characterized by conflict and restrictions. This contrast emphasizes the holy will as a fundamental ethical principle in Kant’s work, playing a key role in shaping his views on morality and human autonomy.